Experimental study on flow characteristics of a large-scale open jet wind tunnel for outdoor pool fire research. Issue 210 (March 2021) - Lei, Jiao; Huang, Pengcheng; Zhang, Linhe; Yuan, Yukui; Deng, Wenyang; Mao, Shaohua; Zhang, Jun
Abstract: An open jet wind tunnel with an exit area of 23 ​× ​9 ​m 2 has been built to study the behaviors of large-scale pool fires under controlled wind conditions. A series of measurements on the mean and fluctuating wind velocities, using arrays of hot-wire probes and ultrasonic anemometers, were extensively performed in the transverse planes at the leading and trailing edges of the pool (28 ​m and 48 ​m to the exit). The entire pool was located in the potential core of the central jet flow region, and the longitudinal velocity ( U ) and turbulence intensity ( I u ) exhibited acceptable uniform distributions within the two vertical planes. The mean turbulence intensities in the two planes were close to those in the flat open grassland and sea (7%–10%). The longitudinal velocity spectra were in good agreement with the Von Kármán spectrum at all levels, and the onset frequency for isotropy was about 1.5–3.0 ​Hz. In the central flow region, the turbulence dissipation rates ( ε ) were fitted well by ε  ​= ​0.067 U 2.69 I u 1.90, and the best-fit line for the turbulent diffusivity ( ν t ) was ν t  ​= ​0.21 U 0.95 I u 0.98 . The detailed mean flow and turbulence characteristics provided the necessary information for the pool fire tests and numerical model verification. Highlights: An open jet wind tunnel (OJWT) with an exit area of 23 m × 9 m was built for outdoor largescale pool fire research. Mean and turbulent flow characteristics of OJWT were investigated with hot-wire probes and ultrasonic anemometers. Mean velocity and turbulence intensity exhibited acceptable uniform distributions in the pool region. Longitudinal velocity spectra fitted well with the Von Kármán spectrum at all levels. Turbulence dissipation rate and turbulent diffusivity were correlated with wind speed and turbulence intensity.